Evaluation of two Empirical Devices for Measurement of Fish Texture - Hassan, Femeena; George, Sajan; Mathew, Saleena; M.K., Mukundan (Fishery Technology, 2025)
Two types of texturometers (weight-operated and spring operated) were fabricated for the evaluation of fish texture. These devices were used to measure the toughness of twenty species of commercially important fishes in raw and cooked conditions. Texture was also evaluated by organoleptic method. A significant positive correlation could be obtained between organoleptic scores and the texturometer readings in the case of fish fillets both in raw and cooked condition.